Survival analysis of women breast cancer patients in Northwest Amhara, Ethiopia - Feleke, Bereket; Tesfaw, Lijalem Melie; Mitku, Aweke A. (Frontiers in Oncology, 2022)
Introduction: Breast cancer is the most common cause of cancer death and the most frequently diagnosed cancer among women worldwide, ranking the second cause of death next to lung cancer. Thus, the main objective was to assess the factors that affect the survival time of breast cancer patients using the shared frailty model. Methods: A retrospective study design was used to collect relevant data on the survival time of breast cancer patients from the medical charts of 322 breast cancer patients under follow-up at Felege Hiwot Comprehensive Specialized Hospital (FHCSH). The data were explored using the Cox proportional hazard model, accelerated failure time model, and shared frailty models. The model comparison was done using AIC and BIC. As a result, the Weibull gamma shared frailty model had a minimum AIC and BIC value. Result: From a total of 322 patients, about 95(29.5%) death and 227(70.5%) were censored. The overall mean and median estimated survival time of breast cancer patients under study was 43.7 and 45 months respectively. The unobserved heterogeneity in the population of clusters (residence) as estimated by the Weibull-gamma shared frailty model was 0.002 (p-value=0.000) indicating the presence of residential variation in the survival time of breast cancer patients. The estimated hazard rate of patients who hadn’t recurrent breast cancer was 0.724 (95% CI: 0.571, 0.917) times the estimated hazard rate of patients who had recurrent breast cancer type. Conclusion: The prevalence of breast cancer was considerably high. Under this investigation, elder patients, patients in stage III and stage IV, anemic and diabetes patients, patients who took only chemotherapy treatment, metastasized patients, patients with AB blood type, patients from positive breast cancer family history, and patients whose cancer was recurrent were with high death rates. Patient characteristics such as age, stage, complication, treatment, metastasis, blood type, family history, and recurrent were the significant factors associated with the survival time of women with breast cancer.